Sensor Placement Optimization of Vibration Test on Medium-Speed Mill - Lihua Zhu; Jun Dai; Guoliang Bai (Shock and Vibration)
Condition assessment and decision making are important tasks of vibration test on dynamic machines, and the accuracy of dynamic response can be achieved by the sensors placed on the structure reasonably. The common methods and evaluation criteria of optimal sensor placement (OSP) were summarized. In order to test the vibration characteristic of medium-speed mill in the thermal power plants, the optimal placement of 12 candidate measuring points in X, Y, and Z directions on the mill was discussed for different targeted modal shapes, respectively. The OSP of medium-speed mill was conducted using the effective independence method (EfI) and QR decomposition algorithm. The results showed that the order of modal shapes had an important influence on the optimization results. The difference of these two methods on the sensor placement optimization became smaller with the decrease of the number of target modes. The final scheme of OSP was determined based on the optimal results and the actual test requirements. The field test results were basically consistent with the finite element analysis results, which indicated the sensor placement optimization for vibration test on the medium-speed mill was feasible.